Cultura & negócios: o jeito Luiza de ser: dimensões simbólicas da cultura na gestão do Magazine Luiza - Silva, Maroni João da (2012)
This dissertation reviews the relations between organizational culture and corporate performance at Magazine Luiza. This retail company is a family business that started operations in the interior of São Paulo state and it has often been under focus by the Brazilian media as it stands out among retail organizations for its flexible, participative management practices. It ranks nowadays among the largest Brazilian corporate players. The Group s history is marked by the new cultural features of the capitalism in a globalized economy, which has led to a new business culture characterized by a flow of images, values and symbols with a multiplicity of meanings. These categories permeate the discourse and management practices of those companies anchored on result generation models based on flexible relations between capital and labor. This essay deals with this matter from an anthropological standpoint with an aim to understand the role played by the symbolic dimensions of culture in the corporate management. It addresses also the relation between Magazine Luiza s cultural management practices and the workers motivations and representations. Moreover, the study identifies the processes through which the employees engage themselves (or not) in the company s formal discourse according to which profit and social well-being are linked to each other by an interdependence relation . For that purpose, the researcher makes use of an ethnographic survey to reconstruct the corporate culture through a participating observation of specific events, like the rites of Communion, Integration and Celebration Meeting. Interviews with managers and workers occupying different positions across Magazine Luiza s organizational structure were quite important to understand a management approach founded on different kinds of expertise. The research shows that the economic results reached by the company are a consequence of actions that have ultimately led to the social construct of the Luiza s Way of Being . Such actions stem from the perception that in order to harmonize the man and the profit it is necessary to implement a management model that contemplates the employees well-being